227k views
3 votes
62,57,52,47,42 recursive formula

62,57,52,47,42 recursive formula-example-1
User Pawelzieba
by
5.6k points

1 Answer

1 vote

Answer:

1st sequence: f(n)=f(n-1)-5 with f(1)=62.

2nd sequence: f(n)=f(n-1)+9 with f(1)=-15.

Explanation:

The first sequence, to get the next term you just subtract 5 from the previous term.

The recursive form is f(n)=f(n-1)-5 with f(1)=62.

The sequence, to get the next term you just add 9 to the previous term.

The recursive form is f(n)=f(n-1)+9 with f(1)=-15.

User Arikon
by
5.8k points